2014
DOI: 10.2147/oaap.s60976
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in arterial blood-gas variables in Holstein calves at moderate altitude

Abstract: The goal of this study was to determine whether peripheral oxygen delivery and efficacy of alveolar-arterial oxygen (A-a O 2) transfer, as estimated from the A-a O 2 pressure gradient, are compromised in Holstein calves at moderate altitude. The primary objective was to evaluate age-related changes in arterial blood-gas variables, L-lactate, and hematocrit in healthy calves. The secondary objective was to determine if coughing and nasal discharge, commonly used indicators of respiratory disease, are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Unlike rodents and other mammals, cattle are reported to be particularly susceptible to hypoxemia due to their small lung volume relative to body mass (Jensen et al, 1976;Veit and Farrell, 1978;Kainer and Will, 1981). Immature lung function (Lekeux et al, 1984;Neary et al, 2014), respiratory compromise, and hypobaric hypoxia (Gulick et al, 2016) could all feasibly contribute toward a hypoxia-induced increase in intestinal permeability with deleterious consequences on animal health. Hypobaric hypoxia, even at the modest altitude of 975 m, appears to have predisposed the normoxic control calves in our study to pulmonary vascular remodeling, as no difference occurred in the proportion of calves with at least mild arterial lesions between those housed under hypoxic conditions versus normoxic controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike rodents and other mammals, cattle are reported to be particularly susceptible to hypoxemia due to their small lung volume relative to body mass (Jensen et al, 1976;Veit and Farrell, 1978;Kainer and Will, 1981). Immature lung function (Lekeux et al, 1984;Neary et al, 2014), respiratory compromise, and hypobaric hypoxia (Gulick et al, 2016) could all feasibly contribute toward a hypoxia-induced increase in intestinal permeability with deleterious consequences on animal health. Hypobaric hypoxia, even at the modest altitude of 975 m, appears to have predisposed the normoxic control calves in our study to pulmonary vascular remodeling, as no difference occurred in the proportion of calves with at least mild arterial lesions between those housed under hypoxic conditions versus normoxic controls.…”
Section: Discussionmentioning
confidence: 99%
“…Holstein-Friesian and Jersey breeds of dairy cattle are known to be susceptible to hypoxia-induced pulmonary hypertension, and subsequent death loss can be problematic in regions over 1,500 m in altitude (Malherbe et al, 2012) and secondary to respiratory compromise (Holt and Callan, 2007). The hypoxic effects of respiratory disease may be particularly deleterious in calves because lung function does not become optimal until approximately 1 yr of age (Lekeux et al, 1984;Neary et al, 2014). By preventing the production of inflammatory cytokines such as TNFα and enzymes such as cyclooxygenase, lipoxygenase, and poly(ADPribose) polymerase-1 (Geraets et al, 2007;Li et al, 2016), quercetin may counter the inflammatory effects of hypoxia (Eltzschig and Carmeliet, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects were also reported in etorphine-immobilised sheep and goats in a study by Izwan et al ( 2018 ). In ruminants, an A-a gradient higher than 10 mmHg indicates suboptimal alveolar–arteriolar oxygen exchange (Neary, Garry & Raabis 2014 ). In the present study, both treatments showed mean A-a gradients greater than 10 mmHg (HE and LE: 36.1 ± 8.1 mmHg and 35.3 ± 10.6 mmHg, respectively) indicating alveolar-capillary unit gas diffusion impairment.…”
Section: Discussionmentioning
confidence: 99%
“…More lung regions become progressively ventilated over time postnatally [ 3 , 4 , 5 , 6 ]. In studies of the new-born calf, the effect of increasing ventilation could so far only be indirectly reconstructed by means of pulse oximetry or arterial blood gas analyses [ 7 , 8 , 9 ]. However, using radiographic observations, early studies on babies showed that complete pulmonary ventilation is achieved after a few breaths to a few hours after birth [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%